Impacts on sewer performance due to changes to inputs in domestic wastewater - Mattsson, Jonathan (Luleå tekniska universitet, Arkitektur och vatten, 2015)
The impacts of changes in domestic wastewater inputs on sewer performance have been debated since the dawn of the great sewer construction movement in the 1850s. Nowadays, typical household wastewater that enters sewers can generally be divided into streams from the WC, shower and/or bathtub, kitchen sink, washing machine and dishwasher. Changes in thecomposition of domestic wastewater entering a sewer will depend on inter alia the properties of the appliances used in the households and householders’ residential habits. Recent such changes with a potentially detrimental impact on sewer performance are increased levels of fat, oil and grease used in kitchen practices; the introduction of kitchen sink food waste disposers;and the installation of domestic water efficient appliances. The overall aim of this thesis was, from an historical perspective, to explore how recent changes to inputs in domestic wastewater can impact performance of sewer systems and how this relates to sewers as future carriers of domestic wastewater.Various methods to examine the aim have been employed. Two questionnaire surveys were distributed. The first was sent out to sewer operators/managers employed at Scandinavian public water utilities to explore their views on the extent of fat, oil and grease in sewer systems.The second was sent to sewer/operators managers employed at public water utilities in Northern Sweden to explore the extent of monitoring of incidents of blockages. Two field studies have also been undertaken. One entailed the investigation of long term impacts on sewer performance from the introduction of food waste disposers in housing areas. The other evaluated which parameters of domestic wastewater could be used to estimate levels of infiltration/ inflow into sewers. In addition, a case analysis was undertaken to assess future impacts on self-cleansing regimes in sewer networks when rural subarctic villages are retrofitted with water efficient appliances. A literature review was performed to identify and analyse studies ...